Pengaruh Customer Relationship Management (CRM) terhadap Kinerja CRM Bank serta Dampaknya terhadap Kepuasan Konsumen (Studi Penerapan CRM pada Perbankan di Kota Makassar) - Andi Mappatompo; M. Syafiie Idrus; Margono Setiawan; Umar Nimran (Jurnal Aplikasi Manajemen, 2012)
The purpose of this study is to explain whether the implementation of Customer Relationship Management (CRM) in banking can improve bank CRM. performance and at the same time create satisfaction to customers. This study examined the relationship between variables that makes this research as an. explanatory research. The research was conducted in Makassar. This study used two stage sampling techniques for collecting the samples. The first stage is the census method on 43 sub-branches of Bank BNI and Bank Mandiri in Makassar city that consisted of 32 sub-branches of Bank BNI and 11 sub-branches of Bank Mandiri. The second stage is the unit observation by using proportional random sampling technique for selecting bank employees interacting directly with customers and using information technology in supporting his/her work. The observation was implemented on 137 respondents. The statistical analysis that is used to test the hypothesis is path analysis. The researcher also conducted in-depth interviews on bank customers to confirm the quantitative results on the influence of the banking performance on customer satisfaction. In more detailed results, this study shows that: first, market orientation influences the performance of the banks; second, information technology does not directly influence the performance of the bank, but it influences indirectly through knowledge; third, information technology influences knowledge; fourth, knowledge affects the performance of the banks; fifth, the banking performance affects customer satisfaction. Overall this study shows that Customer Relationship Management application has an impact on customer satisfaction.Keywords: CRM, market orientation, information technology, knowledge, banking performance, customer satisfaction